PEMENUHAN KEBUTUHAN OKSIGENASI PADA ASMA BRONKIAL DENGAN POLA NAFAS TIDAK EFEKTIF DI RUMAH SAKIT PUTRI HIJAU TK II MEDAN - Barus, Tantiyani; Pangaribuan, Resmi; Tarigan, Jemaulana (LPPM Institut Pendidikan Nusantara Global, 2024)
Background: Bronchial asthma is a chronic condition of the respiratory tract that often causes bronchial narrowing, bronchial hyperresponsiveness, and chronic inflammation. In many cases, patients with bronchial asthma have ineffective breathing patterns that affects negatively on oxygenation. Fulfilling oxygenation in patients with bronchial asthma is done to maintain the metabolism of body cells and the activity of various organs or cells. Objective: This case study research aims to describe the application of nursing care management in patients with bronchial asthma associated with oxygenation fulfillment. Method: This descriptive research is conducted using nursing process approach. The research subjects consist of 2 patients with the same case, namely bronchial asthma patients experiencing ineffective breathing patterns. Results: Based on the nursing evaluation of client I and client 2, it indicates that this condition has been resolved from the first to the third day which is shown by significant progress and the client's health improvement. Conclusion: By fulfilling oxygen, doing high- fowler position, using nebulizer and practicing effective coughing, the problem of oxygenation fulfillment with ineffective breathing patterns can be resolved for patients with bronchial asthma.